Effect of serum MMP-7 on the diagnostic accuracy of biliary atresia: systematic review and meta-analysis - Haojun Wang; Hui Liu; Wanfu Li; Ainiwaer Keranmu; Peng Liang; Yaqi Wang; Tao Zhang; Yeliaman Jiayilawu (Frontiers in Pharmacology, 2025)
BackgroundBiliary atresia (BA) is an obstructive fibrotic disorder that typically progresses to cirrhosis and, ultimately, death in children. Current gold standard diagnostics for BA include intraoperative cholangiography and liver biopsy, both invasive procedures with significant complication risks. Matrix metalloproteinase-7 (MMP-7) has emerged as a highly accurate noninvasive diagnostic biomarker for BA. This study therefore aimed to evaluate the diagnostic utility of serum MMP-7 for BA detection.MethodsWe performed a comprehensive search of English-language databases (PubMed, Web of Science, ScienceDirect) with literature from the inception of these databases through 30 November 2024. Study quality was assessed using the QUADAS-2 tool. Sensitivity, specificity, positive/negative likelihood ratios (PLR/NLR), and area under the receiver operating characteristic curve (AUC-ROC) were calculated using Meta-DiSc 1.4 and STATA 18.0.ResultsThis systematic review and meta-analysis included 13 articles (17 studies) comprising 2,836 serum samples from pediatric subjects. Binary classification model analysis showed pooled sensitivity of 0.93 (95% CI: 0.92–0.94) and specificity of 0.85 (95% CI: 0.83–0.87) for MMP-7. Positive likelihood ratio (PLR) was 7.68 (95%CI: 5.04–11.72), the negative likelihood ratio (NLR) was 0.08 (95%CI: 0.05–0.14), and the diagnosis odds ratio (DOR) was 104.34 (95%CI: 55.97–194.51). AUC was 0.9628. Meta-regression analysis identified publication year as a significant heterogeneity source (p = 0.007). Sensitivity analysis confirmed the robust diagnostic stability of MMP-7 for BA. Significant heterogeneity was observed across studies (I2 = 78.6%). Subgroup analysis by publication year showed that heterogeneity primarily originated from studies published in or after 2023.ConclusionSerum MMP-7 represents a convenient, accurate, and reliable noninvasive biomarker for enhancing BA diagnostic efficiency. However, due to significant heterogeneity, further validation via large-scale, multicenter studies with standardized protocols is needed.Systematic Review Registrationhttps://www.crd.york.ac.uk/PROSPERO/recorddashboard, identifier CRD42024623643.